Pendidikan Spritual Ibadah Puasa : Perspektif Andragogi Sufistik - Athoillah Islamy; Nurul Istiani (Studi Multidisipliner: Jurnal Kajian Keislaman, 2021)
This study intends to explore various forms of spiritual education in fasting during Ramadan. This type of research is a qualitative research in the form of library research with a philosophical normative approach. The data sources used are various scientific literatures, both in the form of books (books) and scientific journal articles related to the discussion of the philosophical values of fasting during Ramadan. Meanwhile, the analytical theory used is the Sufistic andragogy theory in the form of takhalli, tahalli, and tajalli methods. The results of the study conclude that there are three forms of actualizing the value of spiritual education with Sufistic dimensions in fasting that can be carried out by an adult Muslim independently and informally. First, the actualization of takhalli values in the form of character education. Second, the actualization of the value of tahalli in the form of an attitude of social concern and various sunnah practices in the month of Ramadan. Third, the actualization of the value of tajalli in the form of the intensity of faith